An initial investigation of the association between the SARS outbreak and weather: with the view of the environmental temperature and its variation. Issue 3 (11th February 2005) - Tan, Jianguo; Mu, Lina; Huang, Jiaxin; Yu, Shunzhang; Chen, Bingheng; Yin, Jun
Abstract : Objective: To understand the association between the SARS outbreak and the environmental temperature, and to provide a scientific basis for prevention and control measures against it. Methods: The daily numbers of the probable SARS patients and the daily meteorological factors during the SARS outbreak period in Hong Kong, Guangzhou, Beijing, and Taiyuan were used in the data analysis. Ecological analysis was conducted to explore the association between the daily numbers of probable SARS patients and the environmental temperature and its variations. Results: There was a significant correlation between the SARS cases and the environmental temperature seven days before the onset and the seven day time lag corresponds well with the known incubation period for SARS. The optimum environmental temperature associated with the SARS cases was between 16°C to 28°C, which may encourage virus growth. A sharp rise or decrease in the environmental temperature related to the cold spell led to an increase of the SARS cases because of the possible influence of the weather on the human immune system. This study provided some evidence that there is a higher possibility for SARS to reoccur in spring than that in autumn and winter. Conclusion: Current knowledge based on case studies of the SARS outbreak in the four cities suggested that the SARS outbreaks were significantly associated with the temperature and its variations. However, because the fallacy and the uncontrolled confounding effects might have biased the results, the possibility of other meteorological factors having an affect on the SARS outbreaks deserves further investigation.